MEMBANDINGKAN CATATAN PERJALANAN PELANCONG DAN NISAN KUNO KERAJAAN PERLAK, ACEH TIMUR, ACEH: [Compairing Travel Notes and Ancient Nisan Peureulak Kingdom, East Aceh, Aceh] - Ambo Asse Ajis (Berkala Arkeologi Sangkhakala, 2021)
The 11th century AD Armenian text entitled A Journals of the South China Sea refers to the tofonim Peureulak by the name Poure (Armenian) as a rich and valuable port. Marco Polo (1293 / late 13th century AD) was called Ferlec (Portuguese), which was a settlement with an Islamic population that was regularly visited by Islamic traders. The Negarakertagama manuscript of the 14th century AD mentions the name Parllak (Javanese) as one of the vassals of the Majapahit Kingdom. Likewise local texts, especially Hikayat Raja-Raja Pasai, mention that the existence of the Peureulak Kingdom ended when it merged into the power of the Samudera Pasai Kingdom (1297 AD) through the process of marriage. This paper aims to see whether the records of the above improvements have the support of archaeological remains, especially the pre-Pasai Ocean era. The research method is descriptive by comparing information with the existence of archaeological remains of two pieces of data that have the same space and time dimensions, namely the rise of the pre-13th century AD and archaeological remains in the form of ancient pre-Samudera Pasai tombstones. The final conclusion is that the results of the comparison of space and time dimensions show that there is a synchronization that confirms the record that saw the Muslim population in Peureulak before the establishment of the kingdom of Samudera Pasai, which is one of the earliest Islamic cities in Southeast Asia. Teks berbahasa Armenia abad ke-11 Masehi berjudul Suatu Catatan Perjalanan di laut Cina Selatan menyebut toponim Peureulak dengan nama Poure (bahasa Armenia) sebagai pelabuhan yang kaya dan berharga. Marco Polo (1293/akhir abad ke-13 M) menyebutnya Ferlec (bahasa Portugis) yakni sebuah lokasi permukiman berpenduduk Islam yang rutin disinggahi pedagang Islam. Naskah Negarakertagama abad 14 menyebut nama Parllak (bahasa Jawa) sebagai salah satu vasal Kerajaan Majapahit. Demikian juga naskah lokal, khususnya Hikayat Raja-Raja Pasai menyebut eksistensi Kerajaan Peureulak berakhir ketika melebur ke dalam kekuasaan Kerajaan Samudera Pasai (1297 M) melalui proses pernikahan. Tulisan ini bertujuan ingin melihat apakah catatan para pelancong di atas memiliki dukungan tinggalan arkeologis khususnya era sebelum Samudera Pasai. Metode penelitian bersifat deskriptif dengan cara melakukan komparasi informasi dengan keberadaan tinggalan arkeologis dua buah data yang memiliki kedudukan dimensi ruang dan waktu yang sama, yakni catatan pelancong abad sebelum abad 13 dan tinggalan arkeologis berupa nisan-nisan kuno era sebelum Samudera Pasai. Kesimpulan akhirnya bahwa dari hasil perbandingan dimensi ruang dan waktu menunjukan ada singkronisasi membenarkan catatan para pelancong melihat adanya penduduk Islam di Peureulak sebelum berdirinya kerajaan Samudera Pasai, yakni satu kota paling awal yang terislamisasi di Asia Tenggara.